The promotion of oral health within the Healthy School context in England: a qualitative research study - Harris Rebecca V; Pine Cynthia M; Stokes Emma (BMC, 2009)
Abstract Background Healthy Schools programmes may assist schools in improving the oral health of children through advocating a common risk factor approach to health promotion and by more explicit consideration of oral health. The objectives of this study were to gain a broad contextual understanding of issues around the delivery of oral health promotion as part of Healthy Schools programmes and to investigate the barriers and drivers to the incorporation of oral health promoting activities in schools taking this holistic approach to health promotion. Methods Semi-structured telephone interviews were carried out with coordinators of Healthy Schools programmes in the Northwest of England. Interview transcripts were coded using a framework derived from themes in the interview schedule. Results All 22 Healthy Schools coordinators participated and all reported some engagement of their Healthy Schools scheme with oral health promotion. The degree of this engagement depended on factors such as historical patterns of working, partnerships, resources and priorities. Primary schools were reported to have engaged more fully with both Healthy Schools programmes and aspects of oral health promotion than secondary schools. Participants identified healthy eating interventions as the most appropriate means to promote oral health in schools. Partners with expertise in oral health were key in supporting Healthy Schools programmes to promote oral health. Conclusion Healthy Schools programmes are supporting the promotion of oral health although the extent to which this is happening is variable. Structures should be put in place to ensure that the engagement of Healthy Schools with oral health is fully supported.